2002
DOI: 10.1002/jae.680
|View full text |Cite
|
Sign up to set email alerts
|

Incentive effects in the demand for health care: a bivariate panel count data estimation

Abstract: This paper contributes in three dimensions to the literature on health care demand. First, it features the first application of a bivariate random effects estimator in a count data setting, to permit the efficient estimation of this type of model with panel data. Second, it provides an innovative test of adverse selection and confirms that high-risk individuals are more likely to acquire supplemental add-on insurance. Third, the estimations yield that in accordance with the theory of moral hazard, we observe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
3
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 23 publications
7
126
3
2
Order By: Relevance
“…We illustrate the proposed methods by applying them to a sub-sample of a data set originally used by Riphahn et al (2003) to analyse the demand for health care. 5 The data set stems from the German Socio-Economic Panel Study (SOEP, see Wagner et al, 2007) and is an unbalanced panel of 7,293 individual families observed from one to seven times.…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…We illustrate the proposed methods by applying them to a sub-sample of a data set originally used by Riphahn et al (2003) to analyse the demand for health care. 5 The data set stems from the German Socio-Economic Panel Study (SOEP, see Wagner et al, 2007) and is an unbalanced panel of 7,293 individual families observed from one to seven times.…”
Section: Applicationmentioning
confidence: 99%
“…Variable descriptions along with summary statistics are given in Table 1. 6 Whereas Riphahn et al (2003) estimate a bivariate model and consider both the number of doctor visits and the number of hospital visits as dependent variables, we focus on analysing only the number of doctor visits in the last three months. Figure 1 shows a histogram of the dependent variable.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This would correspond to a mixed negative binomial model. [The model used in Riphahn (2003).] If it is assumed that ε it has the G(θ,θ) distribution assumed in Section 2 and u i has a normal distribution with mean zero and standard deviation σ, then we obtain a "true" random effects NB model that parallels the model developed earlier.…”
Section: Models For Panel Datamentioning
confidence: 99%
“…Geil et al (1997) and Riphahn et al (2003), also using data from the SOEP, estimate count data models and provide further evidence in favour of the identifying assumption.…”
Section: Discussionmentioning
confidence: 99%